IMPACT ANALYSIS OF COOPERATIVE LEARNING MODEL APPLICATION TYPE TWO STAY TWO STRAY (TSTS) TOWARD LEARNING OUTCOMES OF MATHEMATICS - Muhammad Nurhusain (STKIP Singkawang, 2017)
This research is a comparative experiment. This study aims to determine the effect of the application of cooperative learning model Two Stay Two Stray (TSTS) towards mathematics learning outcomes through comparison with the results of studying mathematics taught using direct learning model. Population, namely the eighth grade students of SMP Negeri 2 Polong Bangkeng Utara Kabupaten Takalar semester of academic year 2016/2017, with a sample of students in grade VIIIA and VIIIB class. The data were analyzed using descriptive statistical analysis techniques and inferential statistics. Descriptive analysis showed that the average student learning outcomes experimental class at the high category, an average of 80.78 with a standard deviation of 11.28; and the average student learning outcomes control class in middle category with an average score of 73.82 with a standard deviation of 12.98. Inferential analysis results obtained H0 and H1 accepted. It can be concluded with 95% confidence that the results of students 'mathematics learning through cooperative learning model Two Stay Two Stray (TSTS) higher than the results of students' mathematics learning through direct learning model.